2006
DOI: 10.1111/j.1447-0756.2006.00401.x
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of metformin on insulin resistance, androgen concentration, ovulation and pregnancy rates in women with polycystic ovary syndrome following laparoscopic ovarian drilling 
THIS ARTICLE HAS BEEN RETRACTED

Abstract: Metformin improves insulin resistance, reduces androgen levels and significantly increases the ovulation and pregnancy rates in infertile women, following LOD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…A total of 28 RCTs potentially resulted for inclusion in the meta-analysis (22,, but of these 11 studies were excluded. In particular, the abortion rate was not evaluated in two studies (35,50), data on the abortion rate were not available from papers and could not be obtained from the investigators after E-mail contact for five studies (30,37,44,53,54), and it was not possible to contact the corresponding investigators for four studies (31,33,47,49). Thus, a total of 17 RCTs (22, 32, 34, 36, 38-43, 45, 46, 48, 51, 52, 55, 56) were included in the final analysis.…”
Section: Resultsmentioning
confidence: 95%
“…A total of 28 RCTs potentially resulted for inclusion in the meta-analysis (22,, but of these 11 studies were excluded. In particular, the abortion rate was not evaluated in two studies (35,50), data on the abortion rate were not available from papers and could not be obtained from the investigators after E-mail contact for five studies (30,37,44,53,54), and it was not possible to contact the corresponding investigators for four studies (31,33,47,49). Thus, a total of 17 RCTs (22, 32, 34, 36, 38-43, 45, 46, 48, 51, 52, 55, 56) were included in the final analysis.…”
Section: Resultsmentioning
confidence: 95%
“…Serum progesterone (P) level more than 5 ng/ml was considered to indicate confirmation of ovulation. The study showed that Metformin improved insulin resistance, reduced androgen levels, and significantly increased the ovulation and pregnancy rates in infertile women following LOD [25]. In another study, 20 women with PCOS were administered either 2 g of myo-inositol plus 200 mcg folic acid or a placebo of 200 mcg folic acid daily.…”
Section: Discussionmentioning
confidence: 96%
“…Kocak and Ustun [25] carried out a randomized study in 2006 to evaluate the effects of Metformin on insulin resistance, androgen concentration, ovulation rates, and pregnancy rates in infertile women with PCOS. They studied 42 infertile women with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the study [39] showed significant cost effectiveness favouring metformin treatment as metformin was about 20-fold cheaper than LOD. Moreover, no significant benefit in terms of pregnancy or live-birth rates was observed when metformin followed LOD in comparison with LOD alone [40].…”
Section: Metformin and Ovarian Dysfunctionmentioning
confidence: 98%